Competition and artificial intelligence: An Australian policy perspective - Andrew Leigh (Institute of Labor Economics (IZA), 2024)
Artificial intelligence has the potential to be a valuable competitive force in product and service markets. Yet AI may also pose competitive problems. I identify five big challenges that AI poses for competition. (1) Costly chips. (2) Private data. (3) Network effects. (4) Immobile talent. (5) An 'open-first, closed-later' model. These are not just issues for our competition regulators, but also for competition reformers. Just as antitrust laws needed to be updated to deal with the misbehaviour of the oil titans and rail barons of nineteenth century America, so too we may need to make changes in competition laws to address the challenges that AI poses.
Keywords: L40; L63; 330; competition; antitrust; artificial intelligence